Penerapan Metode Discovery Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Aqidah Akhlak di Kelas X MA Al Yusriyah Pangkalan Susu - Ahmad Fuadi; Ummi Suhaimi; Siti Aulia; Nurleli Maulida; Nur Hafiza; Nuurun Ala Nuurin; Muhammad Iqbal Qolbaini; Mhd Ariansyah; Boy Rangga Sinulingga (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This research aims to improve student learning outcomes through the application of the Discovery Learning learning model in moral beliefs in class X MA Al Yusriyah Pangkalan Susu. The research method used was Classroom Action Research (PTK) with 25 students. Data collection was carried out through test and non-test techniques. Preliminary findings show that the learning methods used previously, namely lectures and assignments, cause students to feel bored and less interested, so that the learning outcomes do not reach the Minimum Completeness Criteria (KKM). Through the application of the discovery learning method, the results of the study show an increase in student learning outcomes. In the first cycle, the average student score reached 73 with a success rate of 72%, which did not meet the criteria for research success. In the second cycle, there was a significant increase with an average score of 81 and a success rate of 92%, which was categorized as successful. These results show that the discovery learning learning model is effective in increasing students' interest and learning outcomes.